2016
DOI: 10.18805/ijar.10272
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with abnormal parturition and their effects on production and reproductive performance in Frieswal cattle of India

Abstract: Records of 1024 Frieswal cows maintained at the Military Farm, Meerut, India over a period of 20 years from 1989 to 2008, sired by 91 bulls were included in the present study to assess the incidence and risk factors associated with abnormal parturition like dystocia, stillbirth, premature birth and abortion. The overall incidence of abnormal parturition in this herd of Frieswal was 14.01%, out of which 7.91, 3.99, 1.12 and 0.99% correspond to stillbirth, abortion, dystocia and premature birth. Wald Chi square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Later showed increasing trend across the period and it was the lowest in 2005-07 (22.31±0.42 kg) and highest in 2014-15 (23.92±0.50 kg). Our results corroborated the findings of earlier workers (Bakir et al 2004, Kumar et al 2008. Difference in performance across the periods reflected variation in environmental conditions (temperature and relative humidity), feeding, hygiene and dam management during gestation period (Manzi et al 2012).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Later showed increasing trend across the period and it was the lowest in 2005-07 (22.31±0.42 kg) and highest in 2014-15 (23.92±0.50 kg). Our results corroborated the findings of earlier workers (Bakir et al 2004, Kumar et al 2008. Difference in performance across the periods reflected variation in environmental conditions (temperature and relative humidity), feeding, hygiene and dam management during gestation period (Manzi et al 2012).…”
Section: Resultssupporting
confidence: 91%
“…Heritability of birth weight in the present investigation was medium (0.24±0.08). Similar estimates of heritability (h 2 = 0.21) was also reported by Kumar et al (2008) in Frieswal (crossbred) cattle. Several other authors however reported higher estimate of heritability (h 2 = 0.29) of birth weight in crossbred cattle (Mandal andSachdeva 1999, Singh et al 2011).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The reasons of economic losses due to abnormal calving include increased numbers of days open, reduced longevity, less milk yield and calf loss (Bicalho et al 2008). Kumar et al (2017) assessed the effect of calving abnormalities and found declining trend of production and reproduction performances in Frieswal cows that experienced an abnormal parturition. Fertility problems in dairy animals may be arisen as a consequence of abnormal calvings.…”
Section: Importance Of Functional Traitsmentioning
confidence: 99%